Review and Critique of the Book of Scientific Islamic Economics Theory Building - Vaheed Moghadam (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
One of the most important issues in Islamic economics is how to generate theories and to criticize and praise common economic theories. Research Institute of Hawzah and University and SAMT organization have attempted to take a step forward in this field publishing the third edition of the Book of Scientific Islamic Economics Theory Building in 2012, written by Hojatoleslam Hassan Aghanazari. In this book, the author seeks to provide a way for theory building in Islamic economics by combining the teachings of Islam and the scientific method derived from the philosophy of science, but he faces two fundamental problems: Firstly, Islam, in practice, reduces to dos and don’ts, and thus its existential and epistemic propositions are prevented from playing a role in economics; secondly, by accepting experience as the evaluator and the criterion of being scientific, a proposition extends to the empiricism and its weaknesses, of course, the jurisprudential and ideological discussions of the book, especially the subject of constructions are considered as a step forward in the books of Islamic economics. To illustrate the possibility of theory building in Islamic economics, the book offers two concrete examples of this, though these two theories are more likely to be the Islamization of current economics. Therefore, the present book needs to be thoroughly revised to become an appropriate textbook in the field of Islamic economics.